Kontextualisierung von Terrakotten im spätzeitlichen bis spätantiken Ägypten - Jochen Griesbach; Veit Vaelske (Les Carnets de l’ACoSt)
In the first weekend of December 2013 fifteen archaeologists and Egyptologists from Germany and abroad met at the Martin von Wagner-Museum in Würzburg, to discuss current research on the coroplastic art of ancient Egypt. The meeting, under the auspicies of the Institute for Ancient Studies (Institut für Altertumswissenschaften) of the Julius-Maximilians-Universität Würzburg, was generously funded by the Thyssen-Foundation (Fritz Thyssen Stiftung für Wissenschaftsförderung).